Nizhin rada of 1663 in the pre-revolutionary Russian historiography - Тарасов С. (Видавничо-поліграфічний центр "Київський університет", 2013)
Analyzes the concept of pre-revolutionary Russian historians who have studied the events of Nizhin Rada 1663.

Аналізуються концепції російських дореволюційних істориків які досліджували події Чорної ради 1663 р.
Ніжинська рада 1663 р. в російської дореволюційної історіографії
Keywords: Ruyina; Left-Band Ukraine; Nizhin Rada of 1663; Russian historiography; Руїна; Лівобережжя; Ніжинська рада 1663 р.; російська історіографія